Exploring the association between school-based peer networks and smoking according to socioeconomic status and tobacco control context: a systematic review - H. J. Littlecott; G. F. Moore; M. McCann; G. J. Melendez-Torres; L. Mercken; H. Reed; M. Mann; F. Dobbie; J. Hawkins (BMC, 2022)
Abstract Background Whilst prevalence of youth smoking in middle and high income countries has decreased, inequality has prevailed. The introduction of legislation regulating tobacco use in public spaces varies across countries, impacting the tobacco control context. Thus reviewing our knowledge of how social networks may influence smoking differently within different contexts is required to facilitate the development of context-specific interventions. Methods The search, conducted on 31st May 2019, included the following smoking-related terms; schools, adolescents, peers and social networks. Inclusion and exclusion criteria were applied throughout the title and abstract screening and full text screening. Quality assessment and synthesis followed. Studies were narratively synthesised to identify changes according to legislative context. This synthesis was conducted separately for findings relating to three categories: socioeconomic status; social selection and influence; and network position. Results Thirty studies were included. Differences in the relationship between network characteristics and smoking according to socioeconomic status were measured in five out of fifteen studies in Europe. Results varied across studies, with differences in network characteristics and their association with smoking varying both between schools of a differing and those of a similar socioeconomic composition. For studies conducted both before and after the introduction of comprehensive smoking legislation, the evidence for selection processes was more consistent than influence, which varied according to reciprocity. Findings showed that isolates were more likely to smoke and in-degree and out-degree centrality were related to smoking both before and after the introduction of legislation. The relationship between popularity and smoking was contingent on school level smoking prevalence in studies conducted before the introduction of legislation, but not after. Conclusions Overall, effects according to socioeconomic status were underreported in the included studies and no consistent evidence of change after the introduction of a comprehensive smoking ban was observed. Further network analyses are required using more recent data to obtain a comprehensive understanding of how network processes may influence smoking differently according to socioeconomic status, and how adaptation could be used to enhance intervention effectiveness. Systematic review registration International Prospective Register of Systematic Reviews (PROSPERO) registration number: CRD42019137358 .